Image Management in a Touristic Destination: A Qualitative Approach Analysis of the Border City of Ciudad Juarez, Mexico - Macias, Carlos J. Gonzalez; Martinez, Maria T.; Morales, Santos A. (European Scientific Journal, ESJ, 2017)
This paper summarizes an academic experience. It has been made by the contributions of a group of experts from a Mexican university participating in a discussion panel called "Image of a Touristic Destination". This was done within the framework of the activities carried out during the 8va. Catedra Patrimonial "Sergio Molina" on October 19-21, 2016. The purpose of this paper is to analyze the process of image management of a border touristic destination through the experience of Ciudad JuÃ¡rez, in order to obtain an improvement in it. The concept of image is analyzed from its components of responsibility and participation in management between Government (message), Society (context), and Universities (management). The methodological approach selected was exploratory. The grounded theory method was selected and thematic analysis with the support of the Atlas-ti software was made. Suggestions are offered for actions which seek to highlight the positive aspects of the city as a touristic destination. The importance of generating responsibility and participation within a social network was highlighted. It was recommended to take advantage of the economic and intellectual resources in education of the Juarez society so that they can know their culture and history.